Basic and Therapeutic Aspects of Angiogenesis Updated. Issue 2 (3rd July 2020) - Eelen, Guy; Treps, Lucas; Li, Xuri; Carmeliet, Peter
Abstract : All organisms growing beyond the oxygen diffusion limit critically depend on a functional vasculature for survival. Yet blood vessels are far more than passive, uniform conduits for oxygen and nutrient supply. A remarkable organotypic heterogeneity is brought about by tissue-specific differentiated endothelial cells (lining the blood vessels' lumen) and allows blood vessels to deal with organ-specific demands for homeostasis. On the flip side, when blood vessels go awry, they promote life-threatening diseases characterized by endothelial cells inappropriately adopting an angiogenic state (eg, tumor vascularization) or becoming dysfunctional (eg, diabetic microvasculopathies), calling respectively for antiangiogenic therapies and proangiogenic/vascular regenerative strategies. In solid tumors, despite initial enthusiasm, growth factor–based (mostly anti-VEGF [vascular endothelial growth factor]) antiangiogenic therapies do not sufficiently live up to the expectations in terms of efficiency and patient survival, in part, due to intrinsic and acquired therapy resistance. Tumors cunningly deploy alternative growth factors than the ones targeted by the antiangiogenic therapies to reinstigate angiogenesis or revert to other ways of securing blood flow, independently of the targeted growth factors. In trying to alleviate tissue ischemia and to repair dysfunctional or damaged endothelium, local in-tissue administration of (genes encoding) proangiogenic factors or endothelial (stem) cells harnessing regenerative potential have been explored. Notwithstanding evaluation in clinical trials, these approaches are often hampered by dosing issues and limited half-life or local retention of the administered agents. Here, without intending to provide an all-encompassing historical overview, we focus on some recent advances in understanding endothelial cell behavior in health and disease and identify novel molecular players and concepts that could eventually be considered for therapeutic targeting.